The effect on immunity of long-term intensive training in elite swimmers - Gleeson, M.; McDonald, W. A.; Cripps, A. W.; Pyne, D. B.; Clancy, R. L.; Fricker, P. A. (Clinical & Experimental Immunology, 1995)
The immunological characteristics of elite swimmers were studied over a 7-month training season in preparation for national championships. A non-training control group was used for comparison. It was found that both systemic and mucosal immunity was suppressed in the swimmers. This confirms the general reduction in other-stress tolerance that is a phenomenon associated with intense specific stress adaptation. Implication: Hard-training athletes have increased susceptibility to infection which should always be of concern to athletes and coaches. However, it should be seriously considered particularly at times of major competitions.